Development of a manual of specifications for powdered Annatto dye - Jabonera, Ma. Teresa E.; Gomez, Ma. Theresa L. (1993.)
The study was undertaken with the main objective of developing a manual of specification for annatto powder. In the first phase, the product profile was determined using the Quantitative Descriptive Analysis (QDA) approach. From the results obtained, the powder was characterized as red-orange in color, fine texture, powdery in appearance, and with astringent aroma. The determination of product attributes was done in the second phase. "Mama Sita's" annatto seeds and powder were subjected to objective and sensory tests. Results obtained showed that the raw material was negative for molds and rots but positive for the presence of leaves, twigs and defective seeds. Seeds from batch 1 differed in moisture content from batches 2 and 3, which may be due to insufficient drying upon harvesting. The seeds were found to be low in ash content, poor solubility, with pH range of 5.4 - 5.8 and Munsell reading of 10 R 4/6 to 10 R 4/8, corresponding to reddish orange seeds. On the other hand, the finished product was found to have a much lower moisture and ash, a brighter red-orange color, poor solubility, same pH range with high % water-insoluble solids. The presence of filth such as stones and glossy material was also observed on the finished product. Results of the microbiological tests were positive for molds but negative for lactics and coliforms. Sensory evaluation characterized the powder as light to moderate red-orange color, with moderately fine texture and appearance, with a general acceptability of neither like nor dislike. The sorption isotherm of the product was also determined using the Direct Hygrometric Method. The resulting curve showed that the product is most stable between 44% and 71% relative humidity conditions. Maximum hygroscopicity of the product tends to develop at humidities above 81%. The critical moisture content was found to be 16% on the dry basis.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Annato -- Handbooks, manuals, etc; Dyes and dyeing -- Handbooks, manuals, etc